Answer
To graph \( y = 3(x + 1)^2 - 2 \), start with the parent function \( y = x^2 \). Shift it 1 unit left to \( y = (x + 1)^2 \), then stretch it vertically by a factor of 3 to \( y = 3(x + 1)^2 \), and finally shift it 2 units down to \( y = 3(x + 1)^2 - 2 \). Plot the vertex at \( (-1, -2) \) and additional points to draw the narrower, downward-shifted parabola.
Solution
To graph the quadratic function \( y = 3(x + 1)^2 - 2 \) using transformations, you can follow a step-by-step approach starting from the basic parent function. Here's how you can do it:
### **1. Start with the Parent Function**
The parent function for this quadratic equation is:
\[ y = x^2 \]
### **2. Apply Transformations in Steps**
Transformations alter the parent function by shifting, stretching, or compressing it to obtain the desired graph. We'll apply the transformations one at a time in the following order:
#### **a. Horizontal Shift (Translation)**
**Transformation:** \( y = (x + 1)^2 \)
- **Explanation:** The \( +1 \) inside the parentheses shifts the graph **1 unit to the left**.
- **New Vertex:** The original vertex of \( y = x^2 \) is at \( (0, 0) \). After the shift, the vertex moves to \( (-1, 0) \).
#### **b. Vertical Stretch (Scaling)**
**Transformation:** \( y = 3(x + 1)^2 \)
- **Explanation:** The coefficient **3** multiplies the entire function, causing a **vertical stretch** by a factor of 3. This makes the parabola narrower compared to the parent function.
- **Effect on Vertex:** The vertex remains at \( (-1, 0) \), but the parabola becomes steeper.
#### **c. Vertical Shift (Translation)**
**Transformation:** \( y = 3(x + 1)^2 - 2 \)
- **Explanation:** The \( -2 \) subtracts from the entire function, shifting the graph **2 units downward**.
- **New Vertex:** The vertex moves from \( (-1, 0) \) to \( (-1, -2) \).
### **3. Summary of Transformations**
1. **Start with** \( y = x^2 \) (vertex at \( (0, 0) \)).
2. **Shift left** by 1 unit: \( y = (x + 1)^2 \) (vertex at \( (-1, 0) \)).
3. **Vertical stretch** by a factor of 3: \( y = 3(x + 1)^2 \) (vertex at \( (-1, 0) \), steeper parabola).
4. **Shift downward** by 2 units: \( y = 3(x + 1)^2 - 2 \) (vertex at \( (-1, -2) \)).
### **4. Plotting the Graph**
Here's how you can plot the graph based on the transformed equation:
1. **Plot the Vertex:** Start by plotting the vertex at \( (-1, -2) \).
2. **Determine Additional Points:**
- Choose x-values around the vertex to find corresponding y-values.
- For example:
- **When \( x = -1 \):**
\[ y = 3(-1 + 1)^2 - 2 = 3(0)^2 - 2 = -2 \]
Point: \( (-1, -2) \) (vertex)
- **When \( x = 0 \):**
\[ y = 3(0 + 1)^2 - 2 = 3(1)^2 - 2 = 3 - 2 = 1 \]
Point: \( (0, 1) \)
- **When \( x = -2 \):**
\[ y = 3(-2 + 1)^2 - 2 = 3(-1)^2 - 2 = 3 - 2 = 1 \]
Point: \( (-2, 1) \)
- **When \( x = 1 \):**
\[ y = 3(1 + 1)^2 - 2 = 3(2)^2 - 2 = 12 - 2 = 10 \]
Point: \( (1, 10) \)
- **When \( x = -3 \):**
\[ y = 3(-3 + 1)^2 - 2 = 3(-2)^2 - 2 = 12 - 2 = 10 \]
Point: \( (-3, 10) \)
3. **Draw the Parabola:**
- Plot all the calculated points.
- Draw a smooth, U-shaped curve passing through these points, ensuring it is narrower than the parent \( y = x^2 \) due to the vertical stretch.
- The axis of symmetry is the vertical line passing through the vertex: \( x = -1 \).
### **5. Final Graph Characteristics**
- **Vertex:** \( (-1, -2) \)
- **Axis of Symmetry:** \( x = -1 \)
- **Direction:** Opens **upward** (since the coefficient of \( (x + 1)^2 \) is positive).
- **Width:** **Narrower** than the parent function \( y = x^2 \) due to the vertical stretch by factor 3.
### **6. Visual Representation**
While I can't provide a visual graph here, following the steps above on graph paper or using graphing software will help you accurately plot \( y = 3(x + 1)^2 - 2 \). Here's a quick summary table of points to plot:
| \( x \) | \( y = 3(x + 1)^2 - 2 \) |
|---------|--------------------------|
| -3 | 10 |
| -2 | 1 |
| -1 | -2 |
| 0 | 1 |
| 1 | 10 |
Plot these points and sketch the parabola accordingly.
### **7. Example Using Graphing Software**
If you prefer using graphing tools, entering the equation \( y = 3(x + 1)^2 - 2 \) into graphing software like Desmos, GeoGebra, or a graphing calculator will display the transformed parabola based on the steps outlined above.
---
By understanding and applying these transformations, you can graph a variety of quadratic functions systematically and predict how changes to the equation affect the graph's appearance.
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution